A Guerra do Chaco (1932-1935) e o ensino de história : uma proposta de aulas-oficina para análise da história, cotidiano militar e sujeitos invisibilizados - Sanches, Toni Carlos (2022)
This research aims to contribute to the teaching of History regarding the Chaco War (1932- 1935). We analyzed that there are academic productions on the subject, but there is a gap between production and dissemination in teaching materials. In addition, there remains a certain silence about the subjects who were despised in the historiographical productions about this War, such as women, native peoples and others subordinated in belligerent societies. In this way, we elaborated a paradidactic material, destined to the teachers of Basic Education. The objective is to present, through workshop classes, precisely this war ignored by so many, providing to learn more about the causes of this conflict, its repercussions for Bolivia and Paraguay and for their neighbors in South America, as well as about the invisible subjects of the war, in the perspective Paraguayans and Bolivians. In order to achieve this objective, a bibliographic survey was carried out from Brazilian and foreign productions. Therefore, the research result was divided as follows: in the first chapter we problematize the characteristics of the textbooks and analyze the causes of the absence of the theme in these materials. In the second chapter we analyze the causes of the conflict according to several interpretations, namely: the imperialist vision, outdated but which deserves to be analyzed in certain aspects, the analysis of the Brazilian army officers who participated in the peace negotiations and also in the war at the backstage level. , and finally according to a more comprehensive approach, which does not reject these versions, but seeks to analyze various aspects such as geopolitics and diplomacy. In the third chapter, the subaltern subjects of the war are highlighted: the women nurses who served on the front, the low-ranking officers (pilots of the Paraguayan air force) and the native peoples. Attached, in the format of paradidactic material, the workshop classes are presented in which these subjects ignored by historiographical productions become visible. These workshop classes follow the proposal of using texts and images. They are: 1. Knowing a little about the Chaco War (1932-1935), 2. The importance of the air force in the Chaco War (1932-1935), 3. The participation of women in the Chaco War (1932-1935) ), 4. Combatants in the Chaco War (1932-1935), 5. Native peoples and their participation in the Chaco War, 6. The issue of water in the Chaco War.